Problemy tekstualne, egzegetyczne i translatorskie So 3,18 - Węgrzyniak, Wojciech (Collectanea Theologica, 2018)
The aim of this paper is to analyze Zeph. 3,18, one of the most incomprehensible verses in the book. Firstly, the author describes the near context of the verse, then he examines some variants of the Hebrew manuscripts and the ancient versions. In the next section he presents all the possible solutions dividing them into four groups: 1) based on an emendation of the text; 2) based on semantics, 3) based on its syntax, 4) a diachronic solution. In the conclusion, the author suggests four notions to be applied probably to several instances of crux interpretum of the Bible.